2017
DOI: 10.1186/s13104-017-2686-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the evidence for macrophage presence in skeletal muscle and its relation to insulin resistance in obese mice and humans: a systematic review protocol

Abstract: ObjectivesThe current global rates of obesity and type 2 diabetes are staggering. In order to implement effective management strategies, it is imperative to understand the mechanisms of obesity-induced insulin resistance and diabetes. Macrophage infiltration and inflammation of the adipose tissue in obesity is a well-established paradigm, yet the role of macrophages in muscle inflammation, insulin resistance and diabetes is not adequately studied. In this systematic review, we will examine the evidence for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…As many studies have reported, lncRNAs showed tissue-specific expression patterns across various tissues with the regulatory specificity [45] and presented cell-type-specific expression patterns even in the same tissue [46]. Satellite cells [47], adult stem cells [47], macrophages [48], and vascular endothelial cells [49] reside in the skeletal muscle that possesses a three-dimensional microenvironment. Additionally, skeletal muscle fibers can be classified as fast oxidative-glycolytic, fast glycolytic, slow oxidative as well as various hybrid muscle fibers based on myosin heavy-chain (MHC) isoforms [50].…”
Section: Discussionmentioning
confidence: 95%
“…As many studies have reported, lncRNAs showed tissue-specific expression patterns across various tissues with the regulatory specificity [45] and presented cell-type-specific expression patterns even in the same tissue [46]. Satellite cells [47], adult stem cells [47], macrophages [48], and vascular endothelial cells [49] reside in the skeletal muscle that possesses a three-dimensional microenvironment. Additionally, skeletal muscle fibers can be classified as fast oxidative-glycolytic, fast glycolytic, slow oxidative as well as various hybrid muscle fibers based on myosin heavy-chain (MHC) isoforms [50].…”
Section: Discussionmentioning
confidence: 95%
“…This systematic review has been registered with PROSPERO (registration no. CRD42016033035), and the methods are available in a published protocol . This systematic review follows the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines, and the completed PRISMA checklist is available in Table S1 in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, we hand‐searched reference lists of included studies. A sample of the search strategy was included in the published protocol for this review …”
Section: Methodsmentioning
confidence: 99%
“…All of these tissues have its own specific niche of macrophages having essential physiologic function that sustain integrity of tissues, adapting at every stage of T2D formation. [3][4][5]35,36 Tissue macrophages actions have been demonstrated to be markedly strong regulators of insulin signaling, their sensitivity as well as resistance Figure 4.…”
Section: Metabolic Physiology As Well As Pathology-role Of Tissue Macmentioning
confidence: 99%